Development of Real-Time PCR Methods for the Detection of Bacterial Meningitis Pathogens without DNA Extraction - Vuong, Jeni; Collard, Jean-Marc; Whaley, Melissa J.; Bassira, Issaka; Seidou, Issaka; Diarra, Seydou; Ouédraogo, Rasmata T.; Kambiré, Dinanibè; Taylor, Thomas H.; Sacchi, Claudio; Mayer, Leonard W.; Wang, Xin (PloS one, 2016)
Neisseria meningitidis (Nm), Haemophilus influenzae (Hi), and Streptococcus pneumoniae (Sp) are the lead causes of bacterial meningitis. Detection of these pathogens from clinical specimens using traditional real-time PCR (rt-PCR) requires DNA extraction to remove the PCR inhibitors prior to testing, which is time consuming and labor intensive. In this study, five species-specific (Nm-sodC and -ctrA, Hi-hpd#1 and -hpd#3 and Sp-lytA) and six serogroup-specific rt-PCR tests (A, B, C, W, X, Y) targeting Nm capsular genes were evaluated in the two direct rt-PCR methods using PerfeCTa and 5x Omni that do not require DNA extraction. The sensitivity and specify of the two direct rt-PCR methods were compared to TaqMan traditional rt-PCR, the current standard rt-PCR method for the detection of meningitis pathogens. The LLD for all 11 rt-PCR tests ranged from 6,227 to 272,229 CFU/ml for TaqMan, 1,824-135,982 for 5x Omni, and 168-6,836 CFU/ml for PerfeCTa. The diagnostic sensitivity using TaqMan ranged from 89.2%-99.6%, except for NmB-csb, which was 69.7%. For 5x Omni, the sensitivity varied from 67.1% to 99.8%, with three tests below 90%. The sensitivity of these tests using PerfeCTa varied from 89.4% to 99.8%. The specificity ranges of the 11 tests were 98.0-99.9%, 97.5-99.9%, and 92.9-99.9% for TaqMan, 5x Omni, and PerfeCTa, respectively. PerfeCTa direct rt-PCR demonstrated similar or better sensitivity compared to 5x Omni direct rt-PCR or TaqMan traditional rt-PCR. Since the direct rt-PCR method does not require DNA extraction, it reduces the time and cost for processing CSF specimens, increases testing throughput, decreases the risk of cross-contamination, and conserves precious CSF. The direct rt-PCR method will be beneficial to laboratories with high testing volume.